2011
DOI: 10.1080/14786419.2010.488235
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian propolis: chemical composition, biological activity and botanical origin

Abstract: From a biologically active extract of Indonesian propolis from East Java, 11 compounds were isolated and identified: four alk(en)ylresorcinols (obtained as an inseparable mixture) (1-4) were isolated for the first time from propolis, along with four prenylflavanones (6-9) and three cycloartane-type triterpenes (5, 10 and 11). The structures of the components were elucidated based on their spectral properties. All prenylflavanones demonstrated significant radical scavenging activity against diphenylpicrylhydraz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 18 publications
1
76
0
Order By: Relevance
“…Considering only Pacific propolis, Su et al [19] reported the presence of propolin in Taiwanese propolis and ten phenylpropanoic acid esters were found in Korean propolis [20]. In addition, 11 compounds were reported from Indonesian propolis but, interestingly, not cardol [21]. In this research, we reported how cardol, also a major compound in the Indonesian propolis from at least T. incisa , could induce apoptosis in SW620 cells.…”
Section: Discussionmentioning
confidence: 71%
“…Considering only Pacific propolis, Su et al [19] reported the presence of propolin in Taiwanese propolis and ten phenylpropanoic acid esters were found in Korean propolis [20]. In addition, 11 compounds were reported from Indonesian propolis but, interestingly, not cardol [21]. In this research, we reported how cardol, also a major compound in the Indonesian propolis from at least T. incisa , could induce apoptosis in SW620 cells.…”
Section: Discussionmentioning
confidence: 71%
“…A coupling constant about 12 Hz for H-a and H-b of 3, 4, 5, 8, 9, 15, and 16 suggested the presence of a cis-stilbene core instead of a trans-stilbene. 22 Therefore, compounds 3,4,5,8,9,15, and 16 were elucidated as shown in Fig. 1 and named as macasiamenenes C, D, E, H, I, O, and P, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…1 Some species has been used as a traditional Thai medicine for antipyretic, antitussive and antiinflammatory treatment: 2 phytochemical studies of this genus have revealed a number of phenolic compounds, particularly stilbenoids 3 and flavonoids. 4 Biological investigations of the compounds derived from the Macaranga genus have shown that some compounds exhibit cytotoxic, 3,4 antibacterial, 5 antifungal, 6 a-glucosidase, 7 quinone reductase inhibitory, 8 anti-inflammatory 4,9 or DPPH radical scavenging activities. 4,10 Macaranga siamensis S.J.…”
Section: Introductionmentioning
confidence: 99%
“…In Mongolia, the sole source of propolis appeared to be P. suaveolens, the only poplar growing in this country. In Albania, propolis is collected partially from P. nigra buds, but there are other unidentified sources [17,18]. Typical source of European propolis are poplar tree buds [15] whereas poplar trees can't grow in tropical and subtropical regions.…”
Section: Synthesis and Available Sourcesmentioning
confidence: 99%